Отто Ейхельман: особливості українсько-російських взаємин в системі міжнародних відносин міжвоєнного періоду - Турчин, Ярина (Видавництво Національного університету "Львівська політехніка", 2009)
The political ideas of the famous Ukrainian community activist, lawyer and active participant in the national liberation movement of 1917–1920 Otto Eykhelman are considered. Major attention is paid specifically to analyzing the Ukrainian-Russian relations and also the scholarly opinions regarding the principles of establishing a new world organization with a place for Ukrainian in it.
Keywords: Otto Eykhelman; Ukrainian-Russian relations; inter war period; new world organization